2013
DOI: 10.3748/wjg.v19.i19.2974
|View full text |Cite
|
Sign up to set email alerts
|

Successful liver resection in a giant hemangioma with intestinal obstruction after embolization

Abstract: Hepatic hemangiomas are the most common benign tumor of the liver. Most hepatic hemangiomas remain asymptomatic and require no treatment. Giant hepatic hemangiomas with established complications, diagnostic uncertainty and incapacitating symptoms, however, are generally considered an absolute indication for surgical resection. We present a case of a giant hemangioma with intestinal obstruction following transcatheter arterial embolization, by which the volume of the hemangioma was significantly reduced, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Our outcomes are consistent with those from Vassiou et al, Bailey et al, and Kayan et al, who performed a similar technique with minimal blood loss, improved mobilization, and without inflow vascular occlusion [19][20][21]. Our quantified blood loss was also similar to the 400 mL reported by Zhou et al, who also reported a much longer post-operative stay than our patient (16 days vs. 7 days) [23]. We believe that TAE alone would not be an appropriate treatment option for this patient due to the side effects of TAE monotherapy, risk of future hemangioma complications, and insufficient evidence the patient's symptoms would resolve.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our outcomes are consistent with those from Vassiou et al, Bailey et al, and Kayan et al, who performed a similar technique with minimal blood loss, improved mobilization, and without inflow vascular occlusion [19][20][21]. Our quantified blood loss was also similar to the 400 mL reported by Zhou et al, who also reported a much longer post-operative stay than our patient (16 days vs. 7 days) [23]. We believe that TAE alone would not be an appropriate treatment option for this patient due to the side effects of TAE monotherapy, risk of future hemangioma complications, and insufficient evidence the patient's symptoms would resolve.…”
Section: Discussionsupporting
confidence: 82%
“…Due to the risks associated with TAE and a possible inflammation in the portal triad, some authors advocate for surgical resection either on the same day or within days of the embolization [19,21,34]. Conversely, Zhou et al argue that the timing of surgery should be based on close follow-up with the surgeon and interval imaging, ensuring that the hemangioma has decreased in size [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In complicated hemangioma, transarterial embolization is used before surgery to stabilize ruptured lesion. In an extremely large lesion, Preoperative TAE is widely performed to decrease blood supply and to reduce tumour size making thus definitive surgery easier and less risked [22][23][24][25][26][27]. Radiofrequency ablation was successful to control symptomatic smaller lesions (5-10cm diameter) [28].…”
Section: Non-surgical Therapiesmentioning
confidence: 99%